The effect of betle (Piper betle L.) leaf juice pretreatment on the pharmacokinetics of propranolol on male white rat - Agung Endro Nugroho; Arief Rahman Hakim (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
Drug interaction phenomenon, between drugs on drug and ford (fruit, vegetables on others), can happen in drug therapy of a disease due to the existence of compounds other than the drug (fruits, vegetables or drink). This interaction can alter and affect the action and effect of the drug. The aim of the research is to study an interaction between betle leaf (a vegetable ) and propranolol, which is a beta-blocker with a high hepatic extraction ratio, in male white rat. The study was conducted by employing a completely randomized design in male wistar inbreed rat (aged 2-2.5 months, 150-250 g). The animals in group I were given propranolol with an oral single dose of 7.5 mg/kg BW (control group) and in group II were given pretreatment with betle leaf juice dose of 17 mL/kg BW at an hour prior propranolol administration. After collected at some certain times, the drug concentration on bloods were analyzed with a Spectropflurometer.The results shown that pretreatment of betle leaf juice did not affect the absorption rate constant (Ka) significantly (P>0.05), and increase the total clearence (ClT) and volume of distribution in steady state (Vdss) significantly (P<0.05). The increasing of both ClT and Vdss caused alteration of the secondary pharmacokinetics parameters of propranolol and these derivates significantly(P<0.05) except the mean residence time value (MRT). This it is concluded that the pretreatment of betle leaf juice with the dose of 17 mL/kg BW affect the pharmacokinetics of propranolol or decrease the propranolol concentration in blood.Key words : propranolol, betle leaf, pharmacokinetics and drug interaction